Study on Bioactive Compounds of Jania rubens against Methicillin and Vancomycin Resistant Staphylococcus aureus (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The study is planned to find the antimicrobial activity of the extract of Jania rubens and to isolate the bioactive compound against MRSA and VRSA. Jania rubens collected from Mandapam (Pudumadam) Coastal water, East coast of India and extracted with ethanol. Antibacterial activity of J. rubens was tested against gram positive, gram negative bacteria and drug resistant bacteria). The antibacterial activities were expressed as zone of inhibition, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) Identification of compounds from crude extract of J. rubens carried by column chromatography, thin layer chromatography and NMR analysis. Finally J. rubens could serve as useful source of new antibacterial agent.